Radioimmunoassay of human plasma Lp(a) lipoprotein - Albers, J J; Adolphson, J L; Hazzard, W R (Journal of lipid research, 1977)
A quantitative immunodiffusion assay demonstrated Lp(a) lipoprotein in 91% (911 of 1000) of subjects. In order to quantitate Lp(a) in all plasma, a sensitive and specific double antibody radioimmunoassay was developed. The between-assay coefficient of variation was 8%. Lp(a) levels by radioimmunoassay were highly correlated with those obtained by the less sensitive radial immunodiffusion method (r = 0.98, n = 51). All but one of the 89 Lp(a) “negative” subjects by immunodiffusion had detectable levels of Lp(a) by radioimmunoassay. The one subject without detectable Lp(a) had abetalipoproteinemia (without detectable apolipoprotein B by radioimmunoassay). Furthermore, Lp(a) was detected in all three non-human primates examined: patas monkey, baboon, and pig-tail monkey. Quantitation of Lp(a) levels in 90 male myocardial infarction (MI) survivors and their spouses showed that the distribution of Lp(a) levels of MI survivors was significantly higher above the 50th percentile cut-point (P < 0.02) and exceeded that of the spouses. Furthermore, the Lp(a) distribution at and above the 50th percentile for the MI survivors who had an MI at age <50 (n = 36) was shifted to values higher than those having an MI at age >50. Thus, high levels of Lp(a) may be associated with premature coronary disease. We conclude that Lp(a) is present in all individuals with apolipoprotein B and that apolipoprotein B appears necessary for the plasma transport of the Lp(a) lipoprotein. Consistent with this hypothesis, quantitative immunochemical precipitation of 125I-Lp(a) indicated that essentially all individual molecules of six purified Lp(a) preparations contain both the Lp(a) antigen and apolipoprotein B.